Reading Comprehension in the Medical Education Curriculum during the covid 19: A global Perspective - Ghafar, Zanyar (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The coronavirus caused the global effect of the COVID-19 pandemic, which began in early 2020. Due to the emergence of various infectious illnesses, it is essential for medical students to possess the skills to investigate and treat them. Therefore, it is essential for medical students to peruse the materials provided by the World Health Organisation in order to get a comprehensive understanding of the many symptoms associated with the recently emerged illness, as well as the need for early detection and prevention. Hence, the objective of this study is to emphasise the significance of medical students engaging with novel sources of information and how their proficiency in doing so, whether effective or ineffective, is contingent upon their reading comprehension strategies. Many medical students globally lack sufficient understanding of the recommended infection control practices. Their reading impairments also hindered their comprehension of their medical condition, resulting in delayed diagnosis and inadequate use of preventive medications. The study findings show that, due to the limited scope of medical education programmes, the curriculum for medical colleges did not provide comprehensive instruction on reading comprehension techniques. Currently, there is a lack of comprehensive academic literacy training for medical research in these curricula. Thus, anyone pursuing a medical education should acquire knowledge by studying the resources provided by the World Health Organisation.